Human amniotic membrane for myocutaneous dehiscence after a radical surgical treatment of vulvar cancer: A case report - Restaino, Stefano; Paparcura, Federico; Giorgiutti, Cristina; Trojan, Diletta; Montagner, Giulia; Pengo, Giancarlo; Pividore, Grazia; Albanese, Roberta; Rampino, Emanuele; Dogareschi, Teresa; Bove, Tiziana; Titone, Francesca; et al. (Frontiers in Oncology, 2022)
Background The application of the amniotic membrane could have a favourable effect on tissue repair and regeneration. We report the first case of implant of an amniotic membrane in a patient affected by myo-cutaneous dehiscence, after a radical surgical treatment for vulvar cancer. Methods We describe a case of a 74-years-old patient affected by vulvar cancer. After radiotherapy, the patient underwent to an anterior pelvic exenteration with uretero-ileo-cutaneostomy by Wallace, bilateral pelvic lymphadenectomy, omental biopsies, omental flap, bilateral inguinal lymphadenectomy, resection of ulcerated left inguinal lesion, reconstruction with left gracilis muscle flap and locoregional V-Y advancement flap. The patient developed a myo-cutaneous dehiscence. Two months after the surgery, following an accurate curettage of the wound and negative pressure therapy, a patch of human amniotic membrane was implanted. Results The surgical procedure was easy, feasible and did not require long operating room times. No intraoperative or postoperative complications occurred. The results obtained were encouraging with a marked improvement in the surgical wound. Conclusion the use of amniotic membranes was safely and easily performed to promote the healing of complicated surgical wounds.